The changer of ways: rock art and frontier ideologies on the Strandberg, Northern Cape, South Africa - Skinner, Andrew (My University, 2017)
Southern Africa’s Orange River has been a frontier-zone for centuries, acting as a socially formative and often volatile expression of its surrounds. Communities of the region have competed, compounded, and admixed for as long as competing influences have obliged it, contributing over hundreds of years to a background milieu of generally-coherent beliefs and practices; ‘frontier ideologies’ that dealt in the expression and mediation of identity, and the configuration of responses to tumultuous social and ecological conditions. The common core of these ideologies allowed frontier societies to respond to one another in familiar terms, even if other channels of meaning were inaccessible. One of the contributors to these ideologies were the |Xam, most well-known for their contributions to the shamanistic approach to interpretation of rock art in the Maloti-Drakensberg mountains of South Africa. While analogy has allowed them to speak on behalf of the artists of this disparate tradition, they are products of the area surrounding the Orange River during the nineteenth century. Accordingly, they demonstrate the fundamental features of a frontier society; they evaluate contact with other communities relative to themselves, and formulate appropriate expressions of identity to enact in response. The application of their ethnography is somewhat burdened by their application to the rock art of the Maloti-Drakensberg, however, which casts their motivations in specific, ritualised terms. This thesis considers a very different body of rock art to the one conventionally interpreted by the shamanistic approach, but located in a historical and regional context intimately linked to the |Xam informants; specifically, the rock art of the Strandberg hills, in the Northern Cape province, South Africa. This body of art is one dominated by horses, distributed as a structure that spans much of the site, and manufactured with visibility in mind. This thesis finds that these images were products of the frontier ideologies that inhabited the region, and the adaptive practices that emerge from them. Accordingly, the art is characterised as a record of inhabitation, an expression of identity, and the mediation of contact with a changing landscape, in keeping with the behaviours that had marked interactions between communities in the region for long before many of the images were placed on the Strandberg.
University of the Witwatersrand Submitted in fulfilment of the degree of Master of Science (Archaeology) by research. Rock Art Research Institute; School of Geography, Archaeology, and Environmental Studies. Johannesburg, 2017.
Keywords: Rock paintings--South Africa; Art, Prehistoric--South Africa--Northern Cape